Perfil sorológico de cadelas e respectivas crias: tranferência e declínio de anticorpos passivos contra o vírus da cinomose canina - Patricia Gomes de Souza (1996)
The current study evaluated the transference and duration of matemalantibodies against canine distemper (CDV) in dams and their progenyusing the soroneutralization test. Experiment was camed out with 16bitches of different breeds and their respective offsprings. Serumsamples were collected 48 and 72 hours before parturition, 48 hoursafterwards and every two weeks until the end of the experiment. Inpuppies, serum sample were obtained 48 hours after birth and every twoweeks until eight collects. Neutralization antibodies were detected withserum-neutralization test in cell culture in microtitration plates. Titerswere expressed as inverse semm dilution either as IOQ to which protected 50% of the cell cultures against infection with 100 TCIDSU V"Onderstepoort' strain. The SN titer against CDV in the majority of dams remained fairly constant for the observation period. An increasing of the level of neutralizing antibodies against CDV was observed in two dams 16 and 20 days after parturition; this fact could be due a possible contact with either the virus or vaccine antigen. The SN titers of the dams which were not annually vaccinated were always less than 2 (0,3 log), andconsequently their offsprings not acquired adequately passive matemalantibodies. The percentage of matemal immunity transmission for 16litters from dams varied from 34,0 to 168,0%, with an average of 58%.Great variation was observed in the same litter. Puppies from dam withhigh SN titers against CDV, remained higher titers than those from damwith lower SN titers. A constant and gradual decreasing of seric level ofmatemal antibodies in the puppies ocuned with time increasing, reaching fairly very low levels from 16 days of age.The current study evaluated the transference and duration of matemal antibodies against canine distemper (CDV) in dams and their progeny using the soroneutralization test. Experiment was camed out with 16 bitches of different breeds and their respective offsprings. Serum samples were collected 48 and 72 hours before parturition, 48 hours afterwards and every two weeks until the end of the experiment. In puppies, serum sample were obtained 48 hours after birth and every two weeks until eight collects. Neutralization antibodies were detected with serum-neutralization test in cell culture in microtitration plates. Titerswere expressed as inverse semm dilution either as log10 which protected 50% of the cell cultures against infection with 100 TCID50"Onderstepoort' strain. The SN titer against CDV in the majority of dams remained fairly constant for the observation period. An increasing of the level of neutralizing antibodies against CDV was observed in two dams 16 and 20 days after parturition; this fact could be due a possible contact with either the virus or vaccine antigen. The SN titers of the dams which were not annually vaccinated were always less than 2 (0,3 log), andconsequently their offsprings not acquired adequately passive matemalantibodies. The percentage of matemal immunity transmission for 16litters from dams varied from 34,0 to 168,0%, with an average of 58%.Great variation was observed in the same litter. Puppies from dam withhigh SN titers against CDV, remained higher titers than those from damwith lower SN titers. A constant and gradual decreasing of seric level ofmatemal antibodies in the puppies ocuned with time increasing, reaching fairly very low levels from 16 days of age.